Controllable Design Coupled with Finite Element Analysis of Low‐Tortuosity Electrode Architecture for Advanced Sodium‐Ion Batteries with Ultra‐High Mass Loading. Issue 17 (18th March 2021) - Lv, Zhiqiang; Yue, Meng; Ling, Moxiang; Zhang, Huamin; Yan, Jingwang; Zheng, Qiong; Li, Xianfeng
Abstract: Electrode design enabling more active materials makes it possible to improve the energy density for sodium‐ion batteries (SIBs) on the device level, yet suffer from sluggish ion transport. Herein, a low‐tortuosity Na3 V2 (PO4 )3 ‐based cathode is demonstrated based on a nonsolvent‐induced phase separation method. The targeted low‐tortuosity morphology can be achieved by thermodynamic and kinetic modulation. Benefiting from the structural advantages, the electrode with an ultra‐high mass loading (60 mg cm −2 ) and areal capacity (4.0 mAh cm −2 ) is successfully achieved. Even at a high rate of 10 C, the areal capacity remains 1.0 mAh cm −2 . Comprehensive understanding on the effects of low‐tortuosity architecture to the spatial and temporal distribution of the multi‐physical field parameters has been elucidated by the finite element method. A homogeneous Na + distribution, gentle and uniform local current density, and polarization inside the electrode are illustrated. Combining numerical simulations and experiments, it reveals that the low‐tortuosity architecture can contribute to an impressive ion transport capability and consequently significant improvements in electrochemical performance. This study exhibits a prospective solution for the design and optimization of the low‐tortuosity electrodes with ultra‐high mass loading, which opens a new door for developing advanced SIBs with high energy/power density. Abstract : A low‐tortuosity electrode architecture for advanced sodium‐ion batteries is designed and prepared by a nonsolvent‐induced phase separation derived method. The low‐tortuosity pores contribute to an impressive charge transport capability confirmed by the finite element numerical simulations and charge transfer kinetic analysis and consequently, achieve significant improvements in both electrochemical performance (4 mAh cm −2 ) and mass loading (60 mg cm −2 ).